Singularity Detection of Magnetic Memory Signal of Steel-Cord Conveyor Belt - Qiao Tiezhu; Li Xiaolu; Zhang Xueying (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Metal magnetic memory technology was an important method for detecting the steel-cord conveyor belt early fault, characteristics of magnetic memory signal extraction is critical for judging of the conveyor belt failure. Generally using of magnetic memory signal maximum gradient value can quickly judge the stress concentration zone, but the magnetic memory signal is susceptible to effected by environmental and noise; In view of the weak and non-stationary characteristics of magnetic memory signal, this paper has proposed the singularity detection method based on wavelet transform modulus maximum for metal magnetic memory signal, the method could exactly judged the stress concentration zone of joints and located the fault points of the steel-cord belt, the characteristic gradient of magnetic memory signal and the Lipschitz exponent were extracted. The result of simulation indicated the technology was effectively for judging the stress concentration zone and fault point. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2866